IMPROVING STUDENTS’ ABILITY IN WRITING RECOUNT TEXT USING THINK, TALK, WRITE STRATEGY OF FIRST GRADE AT SMK NEGERI 1 TOLITOLI - Diyenti Rusdin (Jurnal Madako Education, 2018)
The objective of this research was to find out whether the use of Think, Talk, Write Strategy effective to improve students’ ability in writing recount text. An experimental design was used to collect the data, while quantitative approach was used to analyze them. The study was taken by the first grade of SMK NEGERI 1 Tolitoli. It was conducted in one class (X PK 2).The data were obtained through a pre-test and post-test. The result of the analysis showed that Think, Talk, Write strategy contribute greatly to the students in writing recount text. It can be seen by the difference of the mean score between pre-test and post-test. The mean score of pre-test was 61.47 while in the post-test improved up to 78.93. Moreover the Minimum Mastery Criterion of English lesson was 75 (seventy-five). Then the data of both test were analyzed by using T-test, and the result showed that the T-count value 7.510 was greater than T-table value 2.045. It can be inferred that Think, Talk, Write strategy was very effective to improve students’ ability in writing recount text.Key words: Writing ability, Recount text, Think, Talk, Write Strategy.